Agency in the Novel “Wanting Mor” by Rukhsana Khan (2009) - Syahrin, Nada Alfi; Wahyuni, Delvi (Universitas Negeri Padang, 2024)
This research is an analysis of the novel Wanting Mor by Rukhsana Khan (2009). The research aims to analyze the agency shown by Afghan women in facing various oppressions in Afghanistan such as the patriarchal system, traditional social relation, foreign country intervention, and women with disabilities. The research used women's agency theory by Naila Kabeer within feminist literary theory. The form of this research is descriptive qualitative analysis. The data in this research was obtained from the novel Wanting Mor by Rukhsana Khan (2009). The results show that there are three factors lead to the emergence of Agency in Afghan women namely education, personal values, and support. This research also shows that there are three manifestations of women's agency in Afghanistan namely Decision-making, Self-determination, and Self-resilience.